ANALISIS RISIKO RANCANG BANGUN DAN IMPLEMENTASI JARINGAN TERPUSAT TERDISTRIBUSI MELALUI FIBER OPTIK LINGKAR KAMPUS IAIN LHOKSEUMAWE - Rahmat, Rahmat; Nurdin, Nurdin (Universitas Lampung, 2024)
The development of fiber optic network infrastructure in campus environments is becoming increasingly important along with the increasing need for bandwidth to access increasingly high levels of internet content. However, the implementation of this infrastructure is not free from risks which need to be managed well so that the implementation process can run smoothly. Therefore, the author aims to carry out a risk management analysis of implementing fiber optic networks on the IAIN Lhokseumawe campus environment. This research methodology uses a qualitative approach with the steps of risk identification, risk analysis, risk assessment and risk management. The results of this research include identification of risks that may occur during the implementation process, risk analysis, and recommendations for managing these risks. The case study describes the condition of existing network infrastructure, fiber optic network topology planning, and identification of information technology (IT) risks that need attention. Thus, this research is expected to contribute to the development of fiber optic network infrastructure in the campus environment more effectively and well documented